2016
DOI: 10.1111/tri.12864
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing donor-specific antibodies are detrimental to kidney allograft only when persistent after transplantation

Abstract: SUMMARY Donor-specific antibodies (DSA) increase the risk of allograft rejection and graft failure. They may be present before transplant or develop de novo after transplantation. Here, we studied the evolution of preformed DSA and their impact on graft outcome in kidney transplant recipients. Using the Luminex Single Antigen assay, we analyzed the sera on the day of transplantation of 239 patients who received a kidney transplant. Thirtyseven patients (15.5%) had pre-existing DSA detected the day of transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 26 publications
0
24
4
2
Order By: Relevance
“…In addition, they showed worse death-censored graft survival than those without DSA at transplantation [3,4,21,22]. Interestingly and opposite to other studies [23][24][25], we found that preformed DSA correlated with postransplant ABMR even if cleared after transplantation, although this latter group exhibited and intermediate risk.…”
Section: Discussioncontrasting
confidence: 98%
“…In addition, they showed worse death-censored graft survival than those without DSA at transplantation [3,4,21,22]. Interestingly and opposite to other studies [23][24][25], we found that preformed DSA correlated with postransplant ABMR even if cleared after transplantation, although this latter group exhibited and intermediate risk.…”
Section: Discussioncontrasting
confidence: 98%
“…Likewise, the presence of DSA at 1‐year was similar between patients with DSA (with or without AT1R‐abs) and much higher than in the remaining patients. Recently, it has been shown that preformed DSA were deleterious to graft survival only when they persisted after transplantation . Notwithstanding, in our cohort, presence of DSA at 1‐year was not an independent predictor of graft failure.…”
Section: Discussioncontrasting
confidence: 65%
“…Recently, it has been shown that preformed DSA were deleterious to graft survival only when they persisted after transplantation. 36 Notwithstanding, in our cohort, presence of DSA at 1-year was not an independent predictor of graft failure.…”
Section: Discussioncontrasting
confidence: 51%
“…We do not use any specialized immunosuppression protocol for the preformed DSA Recently, there was a report on kidney transplantation that showed preformed DSAs are deleterious to graft survival only when they persist after transplantation. 20 In this prior study, DSA persistence was associated with a higher risk of graft loss and AMR. In the present study, only 2 patients (13.3%) in DSA (+) group showed persistent DSAs after LT in the follow-up period at the time of the biopsy, and this may be due to the fact that there was no significant association between preformed DSA and the outcome of LT in the Cell-based assays are used for lymphocyte cross-matching and have been the gold standard method for decades.…”
Section: Results Of Lymphocyte Cross-matchingmentioning
confidence: 75%
“…Recently, there was a report on kidney transplantation that showed preformed DSAs are deleterious to graft survival only when they persist after transplantation . In this prior study, DSA persistence was associated with a higher risk of graft loss and AMR.…”
Section: Discussionmentioning
confidence: 99%